Effect of Levamisole as an Immunomodulator in Cockerels Vaccinated with Newcastle Disease Vaccine - Sanda, M.E.; Anene, B.M.; Owoade, A. (International Journal of Poultry Science, 2008)
The efficacy of Levamisole Hydrochloride-a standard immunomodulator was tested in cockerel chicks. Forty day old chicks were allocated into two groups A and B. Group A received Levamisole at the recommended dosage of 10.05mg/20 birds for 3 days prior to the NDV vaccinations (B1, LaSota and Komarov). Group B received all the afore mentioned vaccinations but was not treated with Levamisole. Sera samples were analyzed by Heamagglutination Inhibition (HI) tests. The data obtained were analyzed statistically using paired t-test. High antibody titers against NDV were observed in both groups. There was no significant immunostimulation by Levamisole in this study.